Hirabah in the Perspective of the Qur’an and the Indonesian Criminal Code: A Maqasid al-Sharia and Deterrence Theory Analysis - Amalia Husna Islamy; Muhammad Sufiyan; Mohammad Arif (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study examines the relationship between the Qur’anic concept of á¸¥irÄbah and violent theft under Article 479 of Indonesia’s Law Number 1 of 2023 concerning the Criminal Code. While previous studies have discussed á¸¥irÄbah from doctrinal, comparative, and contextual perspectives, they have not sufficiently clarified the limits of equivalence between á¸¥irÄbah and violent theft within Indonesian positive law. This article addresses that gap by employing a qualitative normative method and a functional-comparative framework. The analysis focuses on legal foundations, protected interests, elements of offense, public-security implications, structure of sanctions, and procedural safeguards. The findings show that á¸¥irÄbah and Article 479 KUHP overlap in their concern with violence, intimidation, protection of property, and disruption of public security. However, they differ significantly in legal ontology, scope, penal logic, and normative justification. á¸¤irÄbah is framed as a grave offense against public order and social security, whereas Article 479 KUHP remains doctrinally anchored in the offense of theft aggravated by violence. Within maqÄá¹£id al-sharÄ«”˜ah, the punishment for á¸¥irÄbah is understood as a means of protecting life, property, and public security. Drawing on contemporary deterrence theory, the study argues that the effectiveness of punishment depends not merely on severity but also on certainty, consistency, proportionality, and procedural legitimacy. The article also addresses contemporary human rights concerns surrounding á¸¥udÅ«d punishments, emphasizing due process, evidentiary safeguards, and protection against arbitrary enforcement. The study contributes an integrative model for reading Islamic criminal law and modern criminal law as distinct yet dialogical legal traditions.